Proactive Behavior in Basic Life Support Education for Adolescents in Densely Populated Areas - Permaida Permaida; Uray Pardinan; Widia Sari; Titik Ambar Asmarini; Ina Yuhana; Juanda Mutifa; Nur Rahayu (Journal of Health and Nutrition Research, 2026)
Out-of-hospital cardiac arrest (OHCA) is most common in densely populated. Adolescent students are expected to contribute to the rescue as part of the social fabric. This study aimed to examine changes in the proactive behavior of school adolescents in basic life support education. The research used a pre-experimental design with one group pretest-posttest on 102 respondents at SMK Multimedia Mandiri Jakarta using descriptive and Wilcoxon tests.  The results showed that the respondents were predominantly late-phase adolescents (59.8%), male (79.8%), not family members working in health services (95.1%), and not familiar with basic life support (79.4%); (2) The cooperative behavior of adolescents in basic life support education show an increase in cognitive aspects, with an average pre-test score of 52 (bad) to 83 (excelent) in the average post-test score; (3) The results of proactive behavior show a significant clout on the readiness of adolescents in providing basic life support in the community environment living in densely populated settlements (p<0.001). The proactive behavior of teenage students as part of the community in basic life support education is very important. In addition, this study has implications for the independence and readiness of school adolescents to assist victims of out-of-hospital cardiac arrest (OHCA), especially in densely populated areas.